Medication management after intramedullary nailing of atypical fractures. (June 2017) - Feron, Jean-Marc; Cambon-Binder, Adeline
Abstract: Long term use of bisphosphonates (BPs) in osteoporotic patients may be associated with stress fractures of the sub-trochanteric and shaft area of the femur, so called "atypical" femoral fractures (AFF). Specific diagnosis criteria have been defined with 5 major features; the presence of four of them characterizes the AFF. Once a complete fracture occurred, the best surgical treatment is closed reduction and intra medullary nailing. The BPs treatment should be stopped immediately after an AFF occurred. Dietary calcium and vitamin D status should be assessed, and adequate supplementation prescribed. Principle of combination of a systematic bone anabolic treatment is strongly debated. The recombinant parathyroid hormone 1–34 or Teriparatide ® (TPTD) has an anabolic effect on bone and prevent osteoporotic fractures. Available preclinical and clinical data have also demonstrated the role played by TPTD to enhance bone fracture healing and the potential beneficial effect in impaired fracture healing or specific clinical condition like AFFs. Some authors have proposed in incomplete BP use stress fractures different medical management according the MRI findings. Bone anabolic agents may be promising both to prevent healing complications in AFFs and to promote healing in conservative treatment of incomplete AFFs. More clinical studies are needed to confirm this hypothesis.